2000
DOI: 10.1046/j.1439-0507.2000.00534.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Cryptococcus spp. in excreta of pigeons and pet birds

Abstract: In pooled samples of faeces from 25 pet bird flocks in Thuringia, a high rate of contamination with Cryptococcus neoformans var. neoformans was found. The prevalence of Cr. neoformans in the bird-breeding establishments correlated with the numbers of the different pet bird species in these flocks. The differentiation between varieties of Cr. neoformans by means of proline assimilation and canavanine resistance detection as well as with the aid of Cr. neoformans factor sera, polymerase chain reaction (PCR) fing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 27 publications
1
20
0
3
Order By: Relevance
“…albidus and Cr. laurentii have been occasionally reported as potential pathogens for immunocompromised humans and animals (Kielstein et al, 2000). For the most part, our results are in agreement with those of previous studies on the microflora of droppings of different kinds of birds (Cragg & Clayton, 1971;Criseo et al, 1995) or resident microflora in the cloacae of migratory birds (Cafarchia et al, 2006b).…”
Section: Discussionsupporting
confidence: 93%
“…albidus and Cr. laurentii have been occasionally reported as potential pathogens for immunocompromised humans and animals (Kielstein et al, 2000). For the most part, our results are in agreement with those of previous studies on the microflora of droppings of different kinds of birds (Cragg & Clayton, 1971;Criseo et al, 1995) or resident microflora in the cloacae of migratory birds (Cafarchia et al, 2006b).…”
Section: Discussionsupporting
confidence: 93%
“…At the time of the study, the individual test centers applying routine standard laboratory procedures performed the initial species identification, and species confirmation was performed using Fourier transform infrared spectroscopy (FT-IR). FT-IR has been reported to be a rapid, reliable, and cost-saving tool to identify and differentiate bacteria, dermatophytes, and yeasts (54)(55)(56)(57)(58)(59)(60)(61)(62). An IFS 28/B spectrophotometer (Bruker GmbH, Germany) was used for FT-IRbased identification; the resulting spectra were transformed and evaluated using Opus software from Bruker GmbH, as previously described by Tietz et al (58).…”
Section: Methodsmentioning
confidence: 99%
“…association with birds and their guanos, including in aviaries where multiple species are housed in close proximity (6,7,12,24,26,42,51,54,67,75). These studies have identified specific avian species as carriers for Cryptococcus, but no reason for this specificity has been determined.…”
Section: Vol 6 2007 C Neoformans Mates On Pigeon Guano 955mentioning
confidence: 99%